A hybrid model of magnetorheological dampers based on generalized hysteretic biviscous operators. (August 2018) - Zhao, Xinlong; Wu, Shuangjiang; Pan, Haipeng
Magnetorheological dampers are promising vibration control devices that are widely used for vibration mitigation applications. However, due to the inherent hysteresis of magnetorheological dampers, achieving high performance is a challenging issue because it requires the development of models that can accurately describe the unique characteristics of this hysteresis. In this article, first, a generalized hysteretic biviscous operator is proposed to roughly describe the hysteretic property. Then, the superposition of the weighted generalized hysteretic biviscous operators is performed to model the magnetorheological damper, and modified particle swarm optimization is utilized to regulate the weights. This methodology provides the hybrid model with the advantages of both parametric and non-parametric models. Moreover, the model has a rather simple architecture and can be easily determined. The experimental results demonstrate the feasibility of the proposed method.